Geochemical indices for Zn, Cu, and Co in sediment cores of Coata River, Puno Region, Peru - Matamet, Julio Alejandro Mamani; Matamet, Fanny Roxana Mamani; Bonotto, Daniel (Geochimica Brasiliensis, 2024)
Urban contamination resulting from the dynamics of unplanned cities has generated interest in recent decades due to increased pollutant emissions into the natural environment. The Coata River is a complex ecosystem exposed to a load of substances from urban and industrial development. Significant amounts of waste and pollutant substances are discharged into the river, often without any treatment, contributing to a drastic increase in the concentration of heavy metals that cause impacts and pressures on the environment. In this context, the present study evaluates metal contamination (Zn, Cu, and Co) in three short sediment cores of Coata River, Puno region, Peru. Their total concentration was compared with guideline reference values established by international sediment quality standards and used for calculations of the geochemical indices Enrichment Factor and Geoaccumulation Index. Among the analyzed elements, Zn and Cu present the highest and most varied concentration, while Co shows more homogeneous distribution. The assessment of metal concentration in the sediment analyzed revealed that the abundance order was Zn > Cu > Co. According to environmental criteria, the sediments from the three stations range from moderately to highly contaminated with Zn, while Cu and Co show no contamination and moderate contamination, originating from both geogenic and anthropogenic sources.